2022
DOI: 10.1186/s12889-022-14153-1
|View full text |Cite
|
Sign up to set email alerts
|

Determining factors associated with cholera disease in Ethiopia using Bayesian hierarchical modeling

Abstract: Background Cholera is a diarrheal disease caused by infection of the intestine with the gram-negative bacteria Vibrio cholera. It is caused by the ingestion of food or water and infected all age groups. This study aimed at identifying risk factors associated with cholera disease in Ethiopia using the Bayesian hierarchical model. Methods The study was conducted in Ethiopia across regions and this study used secondary data obtained from the Ethiopian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…However, previous study (that is conducted in Ethiopia from 2019 to 2020), showed that 2,790 cholera cases were recorded of which 68 cholera cases were from southern Ethiopia. This study showed that 224 cholera cases occurred in Guraghe zone (it is one of the 15 zones southern Ethiopia) ( 9 ). This might high number of cholera cases might be because of a high number of daily laborers entering from the nearby boundary (Wolayta Sodo, Goffa, and Hadiya Zone).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, previous study (that is conducted in Ethiopia from 2019 to 2020), showed that 2,790 cholera cases were recorded of which 68 cholera cases were from southern Ethiopia. This study showed that 224 cholera cases occurred in Guraghe zone (it is one of the 15 zones southern Ethiopia) ( 9 ). This might high number of cholera cases might be because of a high number of daily laborers entering from the nearby boundary (Wolayta Sodo, Goffa, and Hadiya Zone).…”
Section: Discussionmentioning
confidence: 96%
“…Central and middle Africa accounted for 43.4% of all deaths on the continent, almost 37.5% of deaths occurred in West Africa, and the remaining 19.1% in East Africa and the Horn of Africa ( 8 ). In Ethiopia 2,790 cholera cases were recorded during 2019–2020 of which 68 cholera cases were from southern Ethiopia ( 9 ). The cholera outbreak continues to pose a threat to public health and is a symbol of social injustice and regression.…”
Section: Introductionmentioning
confidence: 99%